Identifying the Outcomes of Healthy Lifestyles in the Post-COVID-19 Era - Rasoul Raesi; Nader Khalesi; Mahboobeh Safavi; Abasat Mirzaei; Khalil Alimohammadzadeh (Archives of Advances in Biosciences, 2023)
Introduction: This study aims to identify the outcomes of healthy lifestyles during the post-COVID-19 era.